Changing demographic trends among South African occupational therapists: 2002 to 2018 - Lieketseng Ned; Ritika Tiwari; Helen Buchanan; Lana Van Niekerk; Kate Sherry; Usuf Chikte (BMC, 2020)
Abstract Background South Africa's quadruple burden of disease, coupled with health system challenges and other factors, predicts a high burden of disability within the population. Human Resources for Health policy and planning need to take account of this challenge. Occupational therapists are part of the health rehabilitation team, and their supply and status in the workforce need to be better understood. Methods The study was a retrospective record-based review of the Health Professions Council of South Africa database from 2002 to 2018. The data obtained from the Health Professions Council of South Africa was analysed for the following variables: geographical location, population groups, age, practice type and sex. Data was entered on a Microsoft Excel spreadsheet and analysed using the Statistical Package for the Social Sciences (SPSS version 22.0). Results In 2018, there were 5180 occupational therapists registered with the Health Professions Council of South Africa with a ratio of 0.9 occupational therapists per 10 000 population. There has been an average annual increase of 7.1% over the time period of 2002-2018. The majority of occupational therapists are located in the more densely populated and urbanised provinces, namely Gauteng, Western Cape and KwaZulu-Natal. Most of the registered occupational therapists are under the age of 40 years (67.7%). The majority (66%) are classified as white followed by those classified as black and coloured. Females make up 95% of the registered occupational therapists. Nationally, 74.8% of occupational therapists are deployed in the private sector catering for 16% of the population while approximately 25.2% are employed in the public sector catering for 84% of the population. Conclusions Under-resourcing and disparities in the profile and distribution of occupational therapy human resources remain an abiding concern which negatively impacts on rehabilitation service provision and equitable health and rehabilitation outcomes.